Additional descriptions of the plant bug genus Psallus from the Korean Peninsula (Hemiptera: Heteroptera: Miridae: Phylinae) - Duwal, Ram Keshari; Lee, Seunghwan (Zootaxa, 2015)
Three new species of the plant bug genus, Psallus are recognized from the Korean Peninsula: Psallus (Calopsallus) injensis Duwal sp. nov., P. (Hylopsallus) taehwana Duwal sp. nov. and P. (Phylidea) yongdaeri Duwal sp. nov. These species are described with illustrations of male and female genitalic structures. A revised key to known species from the Korean Peninsula, including new species and biological notes are provided. The species, Psallus sanguinarius is observed in the South Korea for the first time.